Visible light driven photosplitting of water using one dimensional Mg doped ZnO nanorod arrays. (3rd September 2020) - Sahoo, Pooja; Sharma, Akash; Padhan, Subash; Thangavel, R.
Abstract: In the present work, we have introduced Mg doped ZnO nanorods based photoanodes for photoelectrochemical water splitting applications. Vertically aligned Mg doped ZnO nanorods were fabricated by sol-gel and hydrothermal technique. The as-prepared nanorod samples exhibited hexagonal wurtzite structure as confirmed from XRD measurements. We achieved a photocurrent density of 0.35 mA/cm 2 at 1.5 V vs. Ag/AgCl for 10% Mg doped ZnO photoanode which is 9 times higher than that of undoped ZnO nanorods (0.03 mA/cm 2 ). Incorporation of Mg resulted in faster charge transport and longer life time of electrons with reduced recombination rate. Mg dopant tuned the optical band gap of ZnO and increased the carrier concentration boosting the PEC performance of the photoanodes. Since seawater is one of the most abundant natural resource on earth, we further carried out seawater splitting of 10MgZ under visible light illumination which indicated its high photostability in natural seawater for 5 h of continuous illumination. Graphical abstract: Image 1 Highlights: We introduced Mg doped ZnO nanorods as photoanodes for solar water splitting. A superior photoelectrochemical performance and better electron lifetime was observed. 10% Mg doped ZnO photoanode exhibited long term photostability in natural seawater.